Compliance of platform X with Indonesia’s 2024 regulation on hoaxes and hate speech - Ramadhan, M. Reza Mahdavikia; Bajari, Atwar; Sjafirah, Nuryah Asri (Manajemen Komunikasi, 2025)
Digital platform features can be a means of increasing hoaxes and hate speech if not regulated by strict policies. Currently, Indonesia has only implemented Presidential Regulation No. 32 of 2024, which specifically regulates the responsibilities of digital platforms through Article 5, which has six points of regulation. This new regulation can be used as a basis to see the responsibility of digital platforms in overcoming hoaxes and hate speech. This research aims to see to what extent digital platform X has been adequate to the demands of the newly implemented regulations. This research uses a qualitative research method with an interpretative paradigm that collects data through documentation studies. The research was conducted by analyzing the policies that have been available on digital platform X and comparing them with the regulations applied. The findings of this study indicate that digital platform X has made efforts to overcome hate speech and hoaxes in accordance with the regulations applied. The efforts made include implementing clear and firm rules and policies, providing reporting features, and collaborating with creators through partnership services. However, there are some efforts that have not been specifically regulated, so further adjustments are needed in order to optimally meet the demands of the applied regulations